A Potential Biomarker of Combination of Tumor Mutation Burden and Copy Number Alteration for Efficacy of Immunotherapy in KRAS-Mutant Advanced Lung Adenocarcinoma - Xiang, Luochengling; Fu, Xiao; Wang, Xiao; Li, Wenyuan; Zheng, Xiaoqiang; Nan, Kejun; Tian, Tao (Frontiers in Oncology, 2020)
Objectives: KRAS mutation is the most common oncogene mutation acting as driver mutation in lung adenocarcinoma (LUAD), and immunotherapy may be a promising therapy for KRAS-mutant LUAD. While the combination of tumor mutation burden (TMB) and copy number alteration (CNA) is poorly understood in KRAS-mutant LUAD, our study is performed to identify and explore a biomarker, combination of TMB and CNA, for accurate prediction of ICI therapy in KRAS-mutant advanced lung adenocarcinoma. Methods: In this study, the mutation and clinical data are download from cBioPortal. We evaluated the correction of KRAS mutation status and the value of TMB and CNA. To explore the predictive value of combination of TMB and CNA, patients were divided into different subgroups based on the cutoff point of TMB and CNA. Results: KRAS mutation with concurrent TP53 or STK11 mutation had higher TMB and CNA than single KRAS mutation. Meanwhile, KRAS mutation subgroup, G12C and G>T, with TP53 or STK11 co-mutation also had higher TMB and CNA. We found that TMB and CNA were independently associated with progression free survival (PFS) and durable clinical benefits (DCB). TMB was positively correlated with ICI response, and high CAN was associated with better benefits. However, TMB alone didn’t distinguish different beneficial KRAS-mutant patients. Notably, when combining TMB and CNA, low TMB and high CNA showed worse outcome of ICI therapy, which suggests combination of TMB and CNA could provide more sensitive and more accurate prediction in KRAS-mutant LUAD. Conclusion: Combination of TMB and CNA can provide more sensible and more accurate prediction for response of immune checkpoint inhibitors than individual factors in KRAS-mutant LUAD. Moreover, low TMB and high CNA can be utilized as a potential biomarker to predict adverse outcome in KRAS-mutant LUAD.